2020
DOI: 10.3390/antiox9121297
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Phenolic Content, Antioxidant Activity and Anti-Inflammatory Capacity of Aqueous and Ethanolic Extracts of Sorghum in Lipopolysaccharide-Induced RAW 264.7 Macrophages

Abstract: Sorghum is an important cereal with diverse phenolic compounds that have potential health promoting benefits. The current study comparatively characterized the phenolic contents of two novel black-seeded sorghum lines (SC84 and PI570481) using different extraction systems (water, ethanol and their acidified counterparts) and evaluated their antioxidant and anti-inflammatory activities. Phenolic compositions were determined by spectrophotometric assays and HPLC analysis. Antioxidant activities were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 54 publications
3
40
1
1
Order By: Relevance
“…Similar results were obtained with different organ extracts of Abeliophyllum distichum by suppressing ROS production and/or inhibiting the activation of protein kinases (ERK1/2) when treating RAW264.7 cells with LPS [5]. Likewise, in LPS-activated RAW2647.7 cells, sorghum extracts inhibited the production of nitric oxide (NO), interleukin-6 (IL-6), and ROS, with ethanolic extracts showing greater anti-inflammatory activity related to tannin content [6]. Berries are a rich source of phytochemicals, especially phenolics, which are well known for their protective activity against many chronic diseases.…”
supporting
confidence: 69%
“…Similar results were obtained with different organ extracts of Abeliophyllum distichum by suppressing ROS production and/or inhibiting the activation of protein kinases (ERK1/2) when treating RAW264.7 cells with LPS [5]. Likewise, in LPS-activated RAW2647.7 cells, sorghum extracts inhibited the production of nitric oxide (NO), interleukin-6 (IL-6), and ROS, with ethanolic extracts showing greater anti-inflammatory activity related to tannin content [6]. Berries are a rich source of phytochemicals, especially phenolics, which are well known for their protective activity against many chronic diseases.…”
supporting
confidence: 69%
“…Black sorghum bran phenolics extract (10% w/v in 50% ethanol) showed an inhibitory effect on TNF-α and IL-1β in lipopolysaccharide-stimulated peripheral blood mononuclear cells at dilutions of 1:100-1:200 and 1:100-1:400, respectively [38]. Hong et al [39] showed that acidified ethanol extracts of sorghum (SC84MX, SC84KS, PI570481) at 50 mg gallic acid equivalent/mL inhibited nitric oxide (NO) production up to 72.45%, 68.32%, and 95.36%, respectively. The increase in the secretion of TNF-α and IL-6 of RAW 264.7 macrophages infected by the bacteria Legionella pneumophila was observed after the treatment of polyphenol extracts of sorghum (PI570481) (0.625 and 1.25 mg/mL) [39].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Hong et al [39] showed that acidified ethanol extracts of sorghum (SC84MX, SC84KS, PI570481) at 50 mg gallic acid equivalent/mL inhibited nitric oxide (NO) production up to 72.45%, 68.32%, and 95.36%, respectively. The increase in the secretion of TNF-α and IL-6 of RAW 264.7 macrophages infected by the bacteria Legionella pneumophila was observed after the treatment of polyphenol extracts of sorghum (PI570481) (0.625 and 1.25 mg/mL) [39]. The mRNA expressions of IL-6 and IL-β of RAW 264.7 macrophage cells were significantly inhibited by the soluble phenolic extracts of the sorghum variety (Tong Za 117) at 300 to 500 mg/mL and 50 to 500 mg/mL, respectively, though a non-toxic mechanism [37].…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…In the studied extracts, tannins were the most dominant polyphenols (11,11,136,11 mg of the epicatechin equivalent/g of sorghum). Sorghum extracts have been more powerful than NO radicals in DPPH scavenging activity [89]. In the meantime, the capacity to inhibit DPPH production seemed much greater as all sorghum extracts compared to a further study with an average of 90% of antioxidant activity against DPPH for three separate genotypes.…”
Section: Antioxidant Activitymentioning
confidence: 85%